Pengaruh Non Performing Loan (NPL), Beban Operasional Pendapatan Operasional (BOPO), Capital Adequancy Ratio (CAR) dan Struktur Kepemilikan terhadap Kinerja Keuangan Bank Tahun 2018-2022 - Sholika, Shinta Anatus; Zaki, Achmad (Universitas Negeri Surabaya, 2024)
The aim of this study is to analyze the effect of NPL, BOPO, CAR, and ROE in BUMN and BUS registered with the OJK during the period of 2018-2022. This study uses a quantitative approach with secondary data obtained from financial statements of banks registered with the OJK. The sample consists of several BUMN and BUSN banks that meet specific criteria, such as having complete financial statements for five consecutive years and being involved in international transactions. Data analysis methods include classical assumption tests and multiple regression analysis using SPSS software version 24. The results show that NPL, BOPO, CAR, and Ownership Structure have a significant effect on ROE. A high NPL negatively impacts ROE by reducing interest income, a high BOPO indicates inefficiency in managing operational costs, a high CAR lowers ROE through reduced credit distribution, and Ownership Structure affects ROE with state-owned banks being more focused on social missions, while private banks prioritize profit maximization. This study suggests that banks should keep NPL low, optimize operational cost management, pay attention to CAR management, and improve corporate governance to support profitability and operational efficiency.